2013
DOI: 10.1074/jbc.m113.477695
|View full text |Cite
|
Sign up to set email alerts
|

Benzalkonium Chloride Accelerates the Formation of the Amyloid Fibrils of Corneal Dystrophy-associated Peptides

Abstract: Background: Formation of amyloid fibrils is accelerated by surfactants such as sodium dodecyl sulfate. Results: Fibrillation of corneal dystrophy-associated peptides was accelerated by benzalkonium chloride, a cationic surfactant widely used in eye drops. Conclusion:The results suggest the potential risk that benzalkonium chloride in eye drops may accelerate amyloid fibrillation. Significance: The results support the view of amylome that most proteins contain amyloidogenic sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…This sharp inflection point is most likely due to the formation of BAC micelles. This value is in good agreement with earlier reports . This uncommon behavior in SERS enhancement may be explained, as shown next, by micelle formation.…”
Section: Resultssupporting
confidence: 93%
“…This sharp inflection point is most likely due to the formation of BAC micelles. This value is in good agreement with earlier reports . This uncommon behavior in SERS enhancement may be explained, as shown next, by micelle formation.…”
Section: Resultssupporting
confidence: 93%
“…6a). 35,38,56 This correlation establishes that, combined with moderate denaturation effects on proteins, various detergents close to the CMC concentration accelerate fibrillation. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 were taken from Kato et al, 56 in which the number after BAC represented the length of alkyl chains.…”
Section: Resultsmentioning
confidence: 74%
“…35,38,56 This correlation establishes that, combined with moderate denaturation effects on proteins, various detergents close to the CMC concentration accelerate fibrillation. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 were taken from Kato et al, 56 in which the number after BAC represented the length of alkyl chains. The values for lysophosphatidic acid (LPA) with β2m were from Pal-Gabor et al 38 Furthermore, disordered proteins or peptides with no significant conformation in the absence of detergents (e.g., keratoepithelin, Aβ, or K3) indicated that the interactions between disordered proteins with detergent molecules slightly below CMC were directly responsible for initiating a fibrillation pathway.…”
Section: Resultsmentioning
confidence: 74%
“…The latter requires that the amount of BAC added be above the critical micelle concentration (CMC). Although the quantities used in the nasal formulations are not specified, the allowable range of BAC in nasal formulations, by USP 34-NF 29 standards, is 0.002–0.02 % w/v, which could allow for micelle formation since the CMC of BAC is 0.0035 % w/v [ 14 ]. Regardless of micelle formation or not, the addition of the cationic surfactant lowers the surface tension at the surface-to-air interface.…”
Section: Resultsmentioning
confidence: 99%